منظومة الحكم في الإسلام أصل اعتقادي أم فرعي اجتهادي؟ - Kalibi, Yusuf Atiyah; Muhammad Husni, Ahmad; Fakhri, Anwar (Journal of Islamic and Human Advanced Research- JIHAR, 2014)
تناولت هذه الدراسة من جوانب السياسية الشرعية املتعلقة بشكل املنظومة السياسية للدولة اإلسالمية، وتكمن مشكلة الدراسة جانبا مهما حول شكل املنظومة السياسية-الدولة واحلكم-يف الدولة اإلسالمية، هل هو أصل اعتقادي اثبت ال يتغري؟ أم فرعي اجتهادي؟ حيث هتدف الدراسة لبيان شكل املنظومة السياسية للدولة اإلسالمية، وبيان مدى مرونة اإلسالم يف قبوله للمستجدات يف منظومته السياسية، وانتهجت الدراسة املنهج االستقرائي جلمع اآلراء يف املسألة، واملنهج التحليلي لتحليل هذه اآلراء واألدلة ومناقشتها، وقد توصلت الدراسة لعدة نتائج أمهها أن املنظومة السياسية اإلسالمية من قبيل الفروع القابلة لالجتهاد، وال حرج من إدخال مستحداثت عليها بشرط موافقتها لروح الشرع وحتقيق املصلحة لألمة. ********************************************************** This study takes a very important aspect about Islamic Politics which is concern the political form for Islamic state, the problem statement for this study lies in the form of political system – countries and rules – is it solid does not change? Or it is can be change and improve? Where this study aims to obvious for the political system for the Islamic Countries, and obvious how can Islam be flexibility in approval the updates in the Political System, and the study approach’s the inductive approach to collect opinions in the subject, and analysis approach to analyzes this opinions and evidences and discussion it, this study will reach to many results, the most important of them that the Islamic Political System is from the branches which accepts diligence, and there is no problem from insert any update on it as long as to approval the spirit of religion and achieve the benefit for people.